Program Insan Dinamik Gerbang Transformasi Sosial 2022 (PIDGTS 2022) / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2022)
Program Insan Dinamik Gerbang Transformasi Sosial 2022 (PIDGTS 2022) was organised by the Program Peduli Pendidikan Team, Faculty of Educational Studies (FES), Universiti Putra Malaysia (UPM) in collaboration with the Educational Planning and Research Division, Ministry of Education Malaysia; Manjung District Education Office, Perak; SMK Dato' Idris, Manjung, Perak; Putra Future Classroom, FES UPM; Academy of Language Studies, Universiti Teknologi MARA, Penang Branch (UiTMCPP); Centre for Management of Waqf, Zakat and Endowment (WAZAN) UPM, and Faculty of Educational Studies Students' Associa-tion (FEDSA), UPM. The two-day event took place at SMK Dato' Idris, Manjung, Perak on 16 and 17 June 2022. Four academic panellists from UiTMCPP and UPM facilitated two parallel sessions with the students on 17 June 2022 in the morning. Essentially, the sessions focused on the main aspects of communication and collaboration, creativity and innovation, higher education and careers as well as mastery of reading skills. All these aspects were integrated and delivered in the forms of lectures, conversations and gamification.